TINGKAT PEMAHAMAN MAHASISWA TERHADAP UNGKAPAN ~MASHOU, ~MASHOUKA AND ~MASENKA - Dewi Saparina Halibanon; Melinda Dirgantini; Miranti Arta Rina (Jurnal Sastra - Studi Ilmiah Sastra, 2019)
Ability to communicate after graduating from Japanese study program is one of the assets in a work situation. Interaction in Japanese is inseparable from the influence of the mother tongue as the first language. Therefore, as a teacher is always required to find the right method of teaching. So it can maximally guide students in understanding the use of Japanese phrases. One of them is an expression of solicitation in Japanese. According to Nitta (1999: 33), there are at least three types of expressions of invitation in Japanese ~masenka, ~ masho and ~ mashouka. The existence of various patterns in the expression of solicitation may result in errors in their use if they do not know the conditions of use of each of those expressions, each of which has conditions that cannot replace each other. The shimasenka form used when the speaker is entirely unaware of any previous information about the invitation and the speaker also does not know whether the speaker will accept it or not. Shimasho is a form of invitation which the speaker was very confident that people whom they were asking will agree with the invitation, while the shimashouka form is the scepticism of the speaker in expressing his will. The joint research on the Japanese solicitation expression conducted by Japanese Prodi University PASIM & Maranatha Christian University was conducted to determine the level of our students' understanding in understanding the expression of Japanese language invitation, so that further as a teacher can find the appropriate teaching method especially in the expression of solicitation, so that it will have a positive impact on the use of Japanese language in the world of work. The research used a qualitative descriptive method. Sources of data on the research obtained from questionnaires in the form of 25 conversation sentences using ~ kanyuu hyougen ~masenka, ~ masho and ~ mashouka. The questionnaire distributed to 56 students of Maranatha Christian University and 28 PASIM students, 2nd, 4th and 6th semesters. From the questionnaire, the wrongest and most correct questions analysed with the JLPT level of each student.